Solitary ecology as a phenomenon extending beyond insular systems: exaptive evolution in Anolis lizards - Velasco, Julián A. (Biol Lett, 2019)
The mechanisms driving phenotypic evolution have been of interest to biologists since Darwin. Ecological release—wherein adaptive evolution occurs following relaxation of constraining selective pressures—and environmental filtering—wherein exaptive traits allow colonization of a new area—have been studied in several insular cases. Anolis lizards, which may exist in solitude or sympatry with multiple congeners, are an excellent system for evaluating whether ecological release and environmental filtering are associated with phenotypic shifts across phylogenetic and geographical scales. Insular solitary Anolis exhibit phenotypic differentiation in body size and sexual size dimorphism—SSD—through exaptive and adaptive evolution, respectively. But, the generality of these effects has not yet been addressed. Here, we analyse the evolution of body size and SSD relative to sympatry in mainland Anolis. We found that mainland species co-occurring with few congeners exhibit uniform body size and greater SSD relative to other random mainland assemblages, consistent with the insular solitary pattern. The locations of evolutionary shifts for both traits do not coincide with evolutionary transitions to decreased levels of sympatry. These results are consistent with exaptive environmental filtering but not adaptive ecological release. Future studies should be conducted at local scales to evaluate the role of these factors in the evolution of solitary existence in mainland and island species.